Anchoring Number Talks - Biro, Katie; Dick, Lara K. (Ohio Journal of School Mathematics, 2019)
Number Talks are a powerful strategy for mathematics classroom discourse. However, much of the work on Number Talks focused on their implementation in upper elementary classrooms. For this article, we propose using Anchor Charts in conjunction with Number Talks to assist early elementary students as they learn how to talk about their mathematical thinking. A classroom teacher's experience is shared along with examples and tips for teachers interested in using Anchor Charts with Number Talks are provided.